First, distribute the -4 on the left side of the equation:
-8x + 44 = 12
Next, subtract 44 from both sides of the equation:
-8x = -32
Finally, divide by -8 to solve for x:
x = 4
Solve multi-step linear equations
-4(2x - 11) = 12
5 answers
Solve multi-step linear equations
-3(-4x - 3) = -27
-3(-4x - 3) = -27
First, distribute the -3 on the left side of the equation:
12x + 9 = -27
Next, subtract 9 from both sides of the equation:
12x = -36
Finally, divide by 12 to solve for x:
x = -3
12x + 9 = -27
Next, subtract 9 from both sides of the equation:
12x = -36
Finally, divide by 12 to solve for x:
x = -3
Solve multi-step linear equations
2x - 4x - 3 = -27
2x - 4x - 3 = -27
First, combine like terms on the left side of the equation:
-2x - 3 = -27
Next, add 3 to both sides of the equation:
-2x = -24
Finally, divide by -2 to solve for x:
x = 12
-2x - 3 = -27
Next, add 3 to both sides of the equation:
-2x = -24
Finally, divide by -2 to solve for x:
x = 12